1999
DOI: 10.1007/s004040050236
|View full text |Cite
|
Sign up to set email alerts
|

Vulvar carcinoma: a retrospective analysis of 80 patients

Abstract: We evaluated the files of 80 women who were treated for vulvar carcinoma. In 13 women radiotherapy was used as primary treatment, in 45 cases postoperatively and in 22 women because of local recurrence. Patients older than 60 years had a significantly worse 5-year survival rate (39%) than younger women (57%) (p = 0.02). The 5-year survival rate for patients with negative nodes was 72% versus 46% for the N1- and 47% for the N2-status, respectively (p = 0.027). The 5-year actuarial survival rate for patients wit… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

1999
1999
2020
2020

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 8 publications
(3 citation statements)
references
References 10 publications
0
3
0
Order By: Relevance
“…With 60 years old as a boundary for the risk factors, foreign studies reported that the incidence of vulvar cancer was in direct proportion with age among women over 60 years old. It was also reported that the number of patients with vulvar cancer was the largest among the women aged from 70 to 79 years old in Greece 12 . However, our analysis showed that the peak period of vulvar cancer was younger than 60 years old in China.…”
Section: Resultsmentioning
confidence: 92%
See 1 more Smart Citation
“…With 60 years old as a boundary for the risk factors, foreign studies reported that the incidence of vulvar cancer was in direct proportion with age among women over 60 years old. It was also reported that the number of patients with vulvar cancer was the largest among the women aged from 70 to 79 years old in Greece 12 . However, our analysis showed that the peak period of vulvar cancer was younger than 60 years old in China.…”
Section: Resultsmentioning
confidence: 92%
“…The incidence of vulvar cancer is the highest between 50 to 59 years of age. It had been reported that over 80% of vulvar cancer patients were over the age of 50 years and over 50% were over the age of 70 years, which indicated that the incidence of vulvar caner peaks in females was 70 years and older 12 . It was unclear what account for the difference in peak incidence age between our observation and prior reports.…”
Section: Discussionmentioning
confidence: 99%
“…Such ectopic tissue may undergo the same physiological and pathological processes found in the normal breast [6][7][8][9] . Most of the reported cases in literature involve malignancy arising from ectopic breast tissue located in the vulva [10] . There are few reports about the benign pathologies in vulva mammary gland.…”
Section: Introductionmentioning
confidence: 99%